ARGOS: A fractioned geosynchronous SAR. (November 2019) - Guarnieri, A. Monti; Bombaci, O.; Catalano, T.F.; Germani, C.; Koppel, C.; Rocca, F.; Wadge, G.
Abstract: A swarm of N Synthetic Aperture Radar (SAR) sensors in a geostationary orbit would provide all-day-all-weather imaging within a continental region, using direct downloading for real time data exploitation. The coherent combinations of the echoes would improve the signal-to-noise ratio by a factor of N 2, leading to metric resolution, 20–40 min minimum observation time, multi-polarimetric and interferometric imaging. Fast evolving events like landslides, floods, soil moisture changes, volcanic activity, co-seismic motions, infrastructure deformations and columnar water-vapor maps would be monitored continuously from space for the first time. The observed area would have a footprint up to a thousand kilometers wide, set using electronic steering, anytime, and anywhere within a continent. In this paper, we take advantage of the preliminary concept definition of the "Advanced Radar Geosynchronous Observation System" ARGOS, to provide applications, scalable extension from a single monostatic SAR to a constellation of active and passive sensors, discussion of launch strategies and Radar payload and comparison with concepts proposed in the literature. Abstract : Highlights: We propose a GEO-SAR swarm for all-day-all-weather continuous imaging. The system provides continental access with sub-hour interferometric revisit. It exploits electric propulsion and lightweight Radars. Both multiple launch or incremental, LEO to GTO transfer are discussed. Sensitivity versus frequency is analyzed by accounting for noise and clutter.